2013
DOI: 10.1371/journal.pone.0069073
|View full text |Cite
|
Sign up to set email alerts
|

Elimination of Metastatic Melanoma Using Gold Nanoshell-Enabled Photothermal Therapy and Adoptive T Cell Transfer

Abstract: Ablative treatments such as photothermal therapy (PTT) are attractive anticancer strategies because they debulk accessible tumor sites while simultaneously priming antitumor immune responses. However, the immune response following thermal ablation is often insufficient to treat metastatic disease. Here we demonstrate that PTT induces the expression of proinflammatory cytokines and chemokines and promotes the maturation of dendritic cells within tumor-draining lymph nodes, thereby priming antitumor T cell respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
134
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(137 citation statements)
references
References 42 publications
(2 reference statements)
3
134
0
Order By: Relevance
“…Development of imagable, targeted nanoparticles may even allow for localized PTT at sites of macrometastases. Perhaps most promising are the initial findings that nanoparticle-mediated hyperthermia induces a systemic cancer-specific immune response in which cytotoxic T-cells are trained to recognize and inhibit distal cancer cells [36], a response that may be strengthened by coupling with immunotherapy [32,39], suggesting the potential to inhibit already formed micro- and macrometastases in human patients.…”
Section: Introductionmentioning
confidence: 99%
“…Development of imagable, targeted nanoparticles may even allow for localized PTT at sites of macrometastases. Perhaps most promising are the initial findings that nanoparticle-mediated hyperthermia induces a systemic cancer-specific immune response in which cytotoxic T-cells are trained to recognize and inhibit distal cancer cells [36], a response that may be strengthened by coupling with immunotherapy [32,39], suggesting the potential to inhibit already formed micro- and macrometastases in human patients.…”
Section: Introductionmentioning
confidence: 99%
“…For example, photothermal therapy (PTT) using gold nanoshells was shown to effectively ablate local tumors, releasing endogenous immunostimulatory molecules and promoting subsequent activation of dendritic cells. 30 Even stronger antitumor immune responses can be achieved by combination therapies. For example, PTT in combination with ICD-inducing chemotherapeutic agents or immunomodulating agents have been shown to synergistically elicit systemic antitumor immunity that can eliminate local tumors directly treated with PTT as well as untreated, disseminated tumors in multiple tumor models.…”
Section: Nanomedicine As Immune-modulating Agentsmentioning
confidence: 99%
“…In addition, Au nanoshells and nanoparticles were also developed for theranostics (NIR-photothermal therapy and imaging) of metastatic tumours by T cell-mediated delivery. 283, 284 The efficiency of T cell-mediated delivery of nanomedicines to tumours increased considerably compared to nanomedicines alone. However, their biodistribution results demonstrated that a large amount of nanomedicines also accumulated on multiple other sites including bone, liver, spleen and lung.…”
Section: Battling Metastases (Secondary) Tumours By Nanomedicinesmentioning
confidence: 99%